運動對孩童認知功能及學業表現的影響：文獻回顧與展望 The Effect of Exercise on Cognitive and Academic Performance: A Review and Prospect - 王駿濠 Chun-Hao Wang; 張哲千 Che-Chien Chang; 梁衍明 Yen-Ming Liang; 邱文聲 Wen-Sheng Chiu; 洪蘭 Daisy L. Hung; 曾志朗 Ovid J.-L; 阮啟弘 Tzeng Chi-Hung Juan (National Taiwan Normal University, 2012)
近年來，許多的科學證據均指出，運動或身體活動的參與確實能夠改善大腦及認知功能的表現。而此效益亦能從孩童的認知及學業上的表現觀察到。然而，隨著科技的進步及文明帶來的便利，使得孩童的身體活動日趨減少。重要的是，不活動的生活型態除了會造成孩童健康上的問題之外，更有研究發現，較低身體適能的孩童在認知或學業表現上也較差。因此，讓社會大眾瞭解運動對孩童的效益是有其重要性。有鑒於此，本研究回顧運動或身體活動對孩童課業表現的影響之相關文獻，並從認知神經科學的角度來探討其效益的神經生理機制，最後針對現今的研究發現剖析、整合並對未來研究提出可行的方向。研究者希望藉此呼籲臺灣教育學界與體育學界重視這些研究並提出未來重要的研究方向，更期待這些知識可對教育學界、體育學界及大眾健康上有實質的助益。 An increasing number of studies have suggested that exercise is associated with improvements in cognitive and brain functioning, and this facilitating effect is also evident from observing cognitive and academic performance in children. However, with the advance and prevalence of science and technology in today's culture, children have become increasingly sedentary. Importantly, sedentary habits during childhood not only influences physical health but also cognitive and academic performance. Based on these findings, we review and discuss the associations between physical activity and exercise, as well as their effects on children's academic performance. We also review studies in the field of cognitive neuroscience to discuss the underlying neural mechanisms of the positive effects of physical exercise. We hope by doing so that this review would draw more attention to this topic from the fields of education and physical education and would generate ideas for future research. It is also our wish that this knowledge would provide practical benefits to the fields of education, physical education, and public health.